A case report of COVID‐19 in an asymptomatic patient with newly diagnosed breast cancer. Issue 6 (9th June 2021) - Cen, Cindy; Shiau, Maria C.; Adams, Sylvia; Schnabel, Freya; Guth, Amber
Abstract: COVID‐19 can be especially dangerous in vulnerable populations such as those with cancer undergoing treatment. When it is discovered in an asymptomatic patient through imaging, there is a paucity of evidence‐based treatment recommendations. Abstract : COVID‐19 can be especially dangerous in vulnerable populations such as those with cancer undergoing treatment. When it is discovered in an asymptomatic patient through imaging, there is a paucity of evidence‐based treatment recommendations.